The frequency of, and predisposing risk factors for, ciprofloxacin-induced neuro-psychiatric adverse drug reactions - Hartinger, Jan; Dvořáčková, Eliška; Mysliveček, Marek; Hrušková, Zdeňka; Šatný, Martin; Zlatohlávek, Lukáš; Křížová, Jarmila; Šíma, Martin; Tesař, Vladimír; Slanař, Ondřej (Bratislavské lekárske listy, 2023)
OBJECTIVES: Ciprofloxacin induces rare neuro-psychiatric adverse drug reactions (ADRs) that are, as yet, not possible to predict due to unknown predisposition factors. BACKGROUND: The aim of the analysis was to assess the frequency of neuro-psychiatric ADRs and to identify potential risk factors that predisposed patients to ciprofloxacin neurotoxicity. METHODS: This observational retrospective study involved the evaluation of the medical records of patients in the Nephrology department and 3rd Internal Clinic of the General University Hospital in Prague. RESULTS: The overall incidence of neurological ADRs was 3.6 %. No neurological ADRs developed in patients aged less than 70 years. The covariates that were significantly more prevalent in the patients who developed neuropsychiatric ADRs were as follows: higher age, a history of neuropsychiatric disorders and the use of anticonvulsants. The administration of drugs from other ATC groups, gender, weight, body mass index, body surface area, renal functions, level of C-reactive protein at the beginning of treatment and the total daily dose/kg did not differ significantly between the two groups. CONCLUSION: Ciprofloxacin neuropsychiatric ADRs are more frequent in older patients with a history of neurologic or psychiatric disorders. No other tested covariates were proven to predispose patients to neuropsychiatric ADRs during treatment with ciprofloxacin (Tab. 2, Ref. 20).